Moral sensitivity and caring behavior in nursing interns: the mediating role of empathy - Chen, Jin yan; Chen, Hong fang; Wang, Xing huan; Zong, Qing zhen; Yao, Zhen zhen (Frontiers in Public Health, 2024)
Background The main purpose of this study is to analyze the relationship between moral sensitivity, empathy, and caring behaviors and to explore the mediating effect of empathy on moral sensitivity and caring behaviors of nursing interns. Methods A cross-sectional survey was conducted from August to September 2022 in which 261 nursing interns from two Grade 3A Hospitals in Xi’an participated. The questionnaires used in the survey include the General Information Questionnaire (GIQ), the Moral Sensitivity Questionnaire—Revised Version translated into Chinese (MSQ R-CV), the Chinese version of the Jefferson Empathy Scale (JSE), and the Chinese version of the Caring Behavior Inventory (C-CBI). The obtained data were analyzed through descriptive statistics, a one-way analysis of variance (ANOVA), and Pearson’s correlation coefficient, and the mediating effect of empathy was tested through structural equations. Results The overall mean of moral sensitivity of nursing interns in two Grade 3A Hospitals in Xi’an is 40.84 ± 8.73, the overall mean of empathy is 100.51 ± 21.56, and the overall mean of caring behavior is (113.81 ± 21.05). Statistical analysis showed that there is a positive correlation between moral sensitivity and caring behavior of nursing interns (r = 0.376, p < 0.01), between their empathy and moral sensitivity (r = 0.336, p < 0.01), and between their empathy and caring behavior (r = 0.394, p < 0.01). The empathy of nursing interns has a mediated effect on the relationship between moral sensitivity and caring behavior. The mediated effect value was 0.14, accounting for 31.82% of the total effect. Conclusion The moral sensitivity of nursing interns can have a direct impact on predicting the caring behavior and indirect influences their caring behaviors mediated by empathy, with the latter effect being mediated by empathy. Therefore, nursing educators and hospital administrators should adopt targeted interventions to improve the moral sensitivity and empathy of nursing interns, which can further prove to be beneficial in improving their caring behaviors, leading to enhanced quality of nursing care and reduced nurse–patient conflicts and finally to a stabilized nursing team.